The resorption of nanocrystalline calcium phosphates by osteoclast-like cells - Detsch, Rainer; et al. (Acta Biomaterialia, 2010)
Nanocrystalline calcium phosphates containing carbonate have a high similarity to bone mineral. The reactions of bone cells (primary osteoblasts and osteoclast-like cells) on these materials as well as on sintered β-tricalcium phosphate and hydroxyapatite (HA) confirmed a good biocompatibility of the nanocrystalline samples. However, osteoclastic differentiation was constrained on the carbonate-rich samples, leading to a small number of osteoclast-like cells on the materials and few resorption pits. The grain size of the calcium phosphate ceramics (nano vs. micro) was less important than expected from to physico-chemical considerations. When comparing the nanocrystalline samples, the highest resorption rate was found for nano-HA with a low carbonate content, which strongly stimulated the differentiation of osteoclast-like cells on its surface. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Bone substitution materials; Calcium phosphate; Osteoblasts; Osteoclast-like cells; Resorption